The reality and aspirations of distance learning among students of the ninth grade in the humanities in light of the Corona pandemic in the village of Abu Ghosh from the students’ point of view - Alhaj Othman, Nora Yacob; Salha, Mohammad Omran (Journal of Educational and Psychological Sciences, 2022)
This study aimed to identify the views of the ninth graders on reality and aspirations for distance learning in light of the Corona pandemic in the village of Abu Ghosh, and the relationship between them. As well as to identify the role of the study variables (gender, subject, level of education of the father and mother), the researchers used the descriptive correlative approach. To achieve the goal of the study, a questionnaire consisting of (6) axes of (40) paragraphs was developed, and its validity and stability coefficient were confirmed. The questionnaires were collected, encoded, entered into the computer and statistically processed using the Statistical Package for Social Sciences (SPSS), and then distributed to an intentional sample of (60) students from the ninth grade students in the village. The results of the study showed that the arithmetic mean of the field of reality was (2.17) with a percentage of (72.2) with a rating (average), and the arithmetic mean of the field of aspirations towards learning was (2.24) and a percentage of (74.7) with a rating (high). It was also found that there are no statistically significant differences in the reality and aspirations of distance learning due to the variable (gender, academic subject, level of education of the father and mother). As well as the existence of a statistically significant relationship between reality and aspirations for distance learning. In light of the results, it is recommended: to encourage and help parents for their children in providing other educational media in addition to simultaneous education; Towards historical and civic documentaries. It is also recommended to promote the generalization of the distance learning strategy after the end of the Corona virus crisis to achieve qualitative leaps in the educational system, by investing the advantages of distance learning in virtual classrooms to apply them in traditional classrooms.
Keywords: Covid-19 pandemic; online learning; social sciences